Feasibility analysis of in-plant control for water minimization and wastewater reuse in a wool finishing textile mill - (:unkn) unknown (TAYLOR & FRANCIS INC, 2004)
This study evaluates the feasibility of water minimization and wastewater reuse for a wool finishing textile mill. The evaluation process is based upon a detailed analysis on water use, process profile and wastewater characterization, indicating a potential for 34% reduction in water consumption and for 23% of wastewater recovery for reuse. Wastewater reuse requires treatment and results in a remaining wastewater stream with stronger character and consequently more costly to treat. The feasibility includes technical considerations for appropriate treatment alternatives and related cost factors for water consumption, treatment for reuse and for discharge either to sewer or to receiving media.
Keywords: in-plant control; sewer charge; treatment cost; wastewater reuse; water minimization; wool finishing textile industry